Negotiating the Identities of Teenage Criminals after Parental Divorce - Kahiking, Jannet Gloria; Maria Goretti Adiyanti; Sri Aryanti Kristianingsih (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Identity negotiation is a crucial process in the development of adolescent self-concept, particularly when disrupted by parental divorce. This study aims to explore the dynamics of identity negotiation among adolescents involved in criminal behavior following family separation, and to identify the key factors influencing this process. A qualitative approach with a case study method was employed to gain in-depth insights into participants’ lived experiences. Data were collected through in-depth interviews and participatory observation involving four male adolescents undergoing rehabilitation due to their involvement in criminal cases. Thematic analysis was conducted to identify meaningful patterns in the identity negotiation process. The findings reveal that parental divorce triggers identity disorientation, characterized by social withdrawal, decreased motivation, and deviant behavior. Identity negotiation occurs in two directions: a negative trajectory involving internalized conflict and delinquency, and a positive trajectory marked by self-reflection and efforts toward personal growth. Contributing factors include emotional instability, lack of parental affection, peer influence, and economic hardship. These results highlight the need for comprehensive psychosocial interventions to support adolescents in navigating post-divorce identity formation and prevent maladaptive behavioral outcomes.